2015
DOI: 10.1590/1983-084x/14_062
|View full text |Cite
|
Sign up to set email alerts
|

Gallic acid as the major antioxidant in pequi (Caryocar brasiliense Camb.) fruit peel

Abstract: ABSTRACT:In this study, ethanol-water extracts of pequi fruit peel were fractionated in order to identify and quantify the major antioxidant present in it. The fractions were subjected to liquid-liquid phase extraction and silica-gel column chromatography, and antioxidant activity was monitored using the 2,2-diphenyl-1-picrylhydrazyl radical-scavenging assay. The purity of the fractions was evaluated using thin-layer chromatography and high-performance liquid chromatography (HPLC). The substance with antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 22 publications
1
8
0
2
Order By: Relevance
“…edulis waste extract, despite the use of the identical extraction parameters. This positive relationship between the concentration of phenolic compounds and antioxidant activity has been observed by other authors [15,36,37].…”
Section: Resultssupporting
confidence: 88%
“…edulis waste extract, despite the use of the identical extraction parameters. This positive relationship between the concentration of phenolic compounds and antioxidant activity has been observed by other authors [15,36,37].…”
Section: Resultssupporting
confidence: 88%
“…Responsible for sequestering chelating metals and free radicals, antioxidants are also present in the pequi peel. The peel is rich in gallic acid, with the potential to eliminate reactive oxygen species and act in the prevention of diseases (Rocha et al, 2015), but commonly discarded. The relationship between the part of C. brasiliense used and the action studied is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that supplementation did not significantly decrease the DNA damage index, but significantly reduced the levels of US-CRP in patients, indicating a decrease in inflammation with the use of C. brasiliense. Rocha et al (2015) evaluated the antioxidant action of the hydroethanolic extract of the pequi peel, observing the extract's ability to eliminate free radicals. His research showed that the extract showed significant antioxidant activity.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…C. brasiliense can be considered safe for use. It presents large quantities of antioxidants such as carotenoids and gallic acid (Rocha et al 2015;Traesel et al 2017b). The peel of the fruit is indicated for its nutritional potential and presenting both antioxidant components and many food applications.…”
Section: Ufp Toxicitymentioning
confidence: 99%